Birds and beasts of ancient Mesoamerica: animal symbolism in the Postclassic period - Milbrath, Susan, editor; Baquedano, Elizabeth, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2023)
Birds and Beasts of Ancient Mesoamerica explores animal symbolism in the Postclassic era, deconstructing the placement and use of animal symbolism in material practices and indigenous cosmology.--Provided by publisher.
Reflections on the scholarship of Cecelia Ford Klein and on animal symbolism in Mesoamerica / Elizabeth Hill Boone -- How to construct a dragon for a changing world: the zoomorph on the Venus Platform at Chichen Itza / Cecelia F. Klein -- Pumas and eagles and wolves, oh my! The appropriation and alteration of Teotihuacan processing predators at Tula / Keith Jordan -- An animal kingdom at Chichen Itza: reconstructing a sculptural tableau at the Sacred Cenote / Cynthia Kristan-Graham -- Frogs and toads in postclassic Mesoamerica / Elizabeth Baquedano -- Coyolxauhqui's serpents: political metaphors in Mexica sculptures / Emily Umberger and Elizabeth Aguilera -- Quail in the religious life of the ancient Nahuas / Elena Mazzetto -- Lessening the sting: huipil power and deadly scorpions / Jeanne L. Gillespie -- Dressed to kill: richly adorned animals in the offerings of the Great Temple of Tenochtitlan / Leonardo López Luján, Alejandra Aguirre Molina, and Israel Elizalde Mendez -- Animal symbolism in calendar almanacs of the Codex Borgia and links to postclassic imagery in Mexico / Susan Milbrath -- The new year pages of the Dresden Codex and the concept of co-essence / Merideth Paxton -- Animal manifestations of the creator deities in the Maya codices and the Popol Vuh / Gabrielle Vail and Allen Christenson -- A New World bestiary in postclassic Mesoamerica / Susan Milbrath.
Keywords: Animals -- Symbolic aspects -- Central America; Animals -- Symbolic aspects -- Mexico; Animals in art; Animals, Mythical -- Central America; Animals, Mythical -- Mexico; Animals, Mythical, in art; Indian art -- Central America; Indian art -- Mexico; Animals -- Mythology -- Central America; Animals -- Mythology -- Mexico; Animals -- Folklore; Symbolism in art; Indians of Central America -- Antiquities; Indians of Mexico -- Antiquities